Hepatitis A and hepatitis E seroprevalence amongst hospital staff in Southwestern Iran: a cross-sectional study - Owrang Eilami; Vahid Tavana; Navid Omidifar; Alireza Heiran (Discover Social Science and Health)
Abstract Objective Hepatitis A virus (HAV) and hepatitis E virus (HEV) are significant causes of acute hepatitis, commonly transmitted through the fecal-oral route. Hospital staff, being at a higher risk of exposure, are considered a vulnerable group. This cross-sectional study aimed to determine the seroprevalence of HAV and HEV among hospital staff in Southwestern Iran. Results The overall seropositive rate of HAV and HEV IgG was 9.9% [95% confidence interval (CI): 6.8, 13.4%] and 12.7% [95% CI: 9.3, 16.5], respectively. No significant differences in HAV seroprevalence were found based on sex (P = 0.227), age (P = 0.967), wards (P = 0.841), and occupational groups (P = 0.304). Similarly, there were no significant differences in HEV seroprevalence based on sex (P < 0.99), age (P = 0.982), and wards (P = 0.517). However, healthcare assistants had a significantly higher positive rate of anti-HEV IgG compared to other occupational groups (P = 0.044). The seropositive rate of HAV was lower among Iranian hospital staff compared to the general population, while the seropositive rate of HEV was comparable. Nonetheless, considering the risk of HAV infection in seronegative staff in the hospital environment, appropriate precautions should be taken in this group.